Flexural behavior of steel and polypropylene fiber-reinforced concrete beams with low longitudinal reinforcement ratios - La Torre Esquivel, Darwin (2025)
The use of fiber-reinforced concrete in structural applications is currently under development. It has been proven that high steel fibers and low reinforcing steel lower the structure's ductility since localized cracks are generated. It is hypothesized that this can be solved by using less rigid fibers such as polypropylene. In this research, a comparative study of the influence of synthetic and metallic fibers in normal resistance reinforced concrete with a low reinforcement ratio is carried out. This study focuses on the structural behavior and development of cracking at the service limit state (ELS) and the ultimate limit state (ELU). To this end, an extensive experimental campaign was conducted, comprising, first, the characterization of the material and, second, the testing of reinforced concrete beams. The variables used are (1) the material of the fibers: polypropylene (PP) and steel (ST), (2) the volume of fibers: 0.33 %, 0.66 % and 1.00 %, and (3) the size of the beams: 1.6 and 3.2 m long. The results show that concrete with 1 % steel fibers exhibited higher post-cracking stiffness than with PP fibers, increasing by 104 % and 71 % in 4.00 m beams, respectively, due to its greater residual strength. A higher fiber volume (1 %) increased the yield moment by up to 50 % and the maximum load by 22 %-25 %. However, it reduced ductility, especially with 1 % steel fibers, where it decreased by up to 63 % in 1.60 m beams due to crack localization. In 4.00 m beams, fiber-reinforced concrete showed better flexural performance, with similar maximum load increases as in 1.60 m beams, but with a smaller ductility reduction (24 % with steel fibers and 11 % with PP fibers), indicating that the greater span promotes better strain redistribution.